ANN Control Based Variable Speed PMSG-Based Wind Energy Conversion System - Praveenkumar, B; S.Srikanth, K; Kiran kumar, M; G .Raja sekhar, G (International Journal of Engineering and Technology, 2018)
This paper presents a comparative analysis of three control algorithms for a wind turbine generator using a variable speed permanent magnet synchronous generator (PMSG). The design methodologies of the conventional PI based controller, the Taylor series expansion linear approximation based (TSLA-based) controller and the feedback linearization based (FL-based) nonlinear controller are provided. The objective is to keep the wind turbine operating at normal speed of the rotor at maximum power extraction (MPPT control), while insuring the power extracting from the turbine to the generator, regardless of the wind speed. The controller gains of the nonlinear controller are extended with Artificial Intelligence controller approach. The results show a better control performance for the ANN controller. This performance of Ann controller can be characterized by fast and smooth transient responses as well as a zero steady state error and reference tracking quality.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â